Seeding method and rate influence on weed suppression in aerobic rice - Anwar, Parvez; Juraimi, Abdul Shukor; Puteh, Adam; Selamat, Ahmad; Man, Azmi; Abdul Hakim, (Academic Journals, 2011)
High weed pressure is amongst the major constraints to the extensive adoption of aerobic rice system as a water-wise technique. Towards developing a sustainable weed management strategy, seeding method and rate may substantially contribute to weed suppression and reduce herbicide use and weeding cost. A trough experiment was established at the Plant House of Universiti Putra Malaysia with two seeding methods, namely conventional broadcast seeding (CBS) and line seeding with east-west row orientation (REW). Three seeding rates were established at 200 (SR200), 300 (SR300) and 400 seeds m-2 (SR400); and two weed control levels were established as weedy (W) and weed free (F) in a factorial RCBD with four replications. Twenty (20) weed species comprising eleven broadleaved, five grasses and four sedges were identified. Broadleaved weeds contributed more than 50% of the total dry matter. Weed density and dry weight decreased gradually with increased seeding rate, but were independent of methods. REW produced significantly higher grain yield compared with CBS. Among the seeding rates, SR300 produced the highest grain yield followed by SR200 and SR400. Weed free treatment performed better with a yield advantage of 23% over weedy treatment. Weed inflicted relative yield loss did not vary due to seeding methods or rates. Therefore, increasing seeding rate up to 300 seeds m-2 may be worthwhile to reduce weed pressure without sacrificing rice yield.